Maturity onset diabetes of the young in pregnancy: diagnosis, management and prognosis of MODY in pregnancy. Issue 5 (May 2017) - Rees, Kate; Reed, A.; Banerjee, Anita; Pasupathy, Dharmintra
Abstract: Current management guidelines of diabetes within pregnancy do not differentiate between the underlying physiological dysfunctions that lead to dysglycaemia and provide generic guidance. Specific forms of diabetes in pregnancy require targeted treatment. Maturity onset diabetes of the young (MODY), caused by single gene mutations, is the most common identifiable variant and presents a significant challenge if the mutation is possessed by mother and not inherited by the fetus. Greater awareness of MODY and its subtypes will allow earlier detection and a better prognosis. Although genetic testing is rare, analysis by clinical phenotyping can provide a sensitive and cost effective solution.